Reflecting on 35 years of constructions - Sommerer, Lotte; Hartmann, Stefan (Constructions, 2024)
The well-known conceptual metaphor ‘THEORIES ARE BUILDINGS’ (Lakoff & Johnson, 1980) suggests that theories are developed, rather than born. As such, it is impossible to pinpoint an exact point in time when a particular theory came to life. Nevertheless, the publication of Lakoff’s There - study (1987) or Fillmore, Kay & O’Connor’s Let alone - paper (1988) can be seen as two of the key starting points of Construction Grammar, which has since grown into a broad and diverse field of research (e.g. Hoffmann & Trousdale 2013; Boas 2021). The papers just mentioned already established a number of central ideas that were later spelled out in more detail in Goldberg’s (1995) seminal monograph, which arguably consolidated the field and helped establish it as a major linguistic framework in its own right. We want to use the 35th anniversary of Fillmore et al.’s paper as an opportunity to discuss the current state-of-the-art in Construction Grammar by engaging with constructional Classics (papers and monographs) that have shaped the framework over the last decades (e.g. Michaelis and Lambrecht 1996; Israel 1996; Jackendoff 1997; Croft 2001; Tomasello 2003; Cappelle 2006; among many others). We therefore invite authors to submit empirical studies as well as non-empirical think-pieces which take a cue or concept from these early influential papers and discuss to what extent the ideas hold up in more recent approaches, especially in the light of new empirical evidence. The idea is that the original arguments and ideas are briefly summarized after which the authors present their own research (critically) reflecting on the concept(s) highlighted and proposed in the key papers. It is also up to the contributors to freely choose a ‘younger’ key paper for discussion and explain why they consider their choice seminal